Pengetahuan Ibu Tentang Gizi Balita Dengan Status Gizi Balita Di Puskesmas Karangdadap Pekalongan - Andriyani, Lulu Triska; Ersila, Wahyu (Direktorat Politeknik Kesehatan Makassar, 2024)
Toddlers aged 12-59 months are vulnerable to nutritional and health problems. This can occur because the basal metabolic rate (BMR) is higher in toddlers so that their energy needs are greater and can affect the nutritional status of stunting. In addition, inappropriate parenting patterns and methods of giving food by parents to children are one of the things that increase the risk of malnutrition. The purpose of this study was to determine the relationship between the nutritional condition of toddlers and maternal awareness of toddler nutrition. The study, which was conducted in November and December 2023 in the working area of ​​the Karangdadap Health Center, Pekalongan Regency, was a descriptive correlative cross-sectional study. The research sample consisted of 139 respondents or toddlers aged 12-59 years. The independent variable studied was maternal knowledge, while the dependent variable was the nutritional status of toddlers. The data processing and analysis method used in this study was the Spearman rank test. Based on the survey results, 85.7% of mothers who had sufficient information had children with normal development. There is a relationship between maternal knowledge about toddler nutrition and toddler nutritional status, with a correlation coefficient value of 0.287, indicating that the strength of the relationship is sufficient. The statistical test results obtained a p value = 0.001, thus the p value is smaller than alpha (0.05). Mother's knowledge affects the nutritional status of toddlers, therefore increasing the mother's understanding is important. It is expected that health workers should intensify counseling programs on toddler nutritional needs and motivate mothers to provide nutritional intake according to toddler needs and increase the frequency, diversity/empowerment of toddler nutrition.. Keywords: Maternal knowledge, Nutritional status, toddlers